The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.5962/bhl.title.32405
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption, bioaccumulation and food chain transfer of organic chemicals : report prepared by F. A. P. C. Gobas and D. Mackay

Abstract: The final three chapters of the report present a series of calculation procedures for bioconcentrat ion and biomagni f icat ion and laboratory methods for the investigation of bioconcentration phenomena. A comprehensive bibliography of approximately 120 references, as well as an appendix of selected relevant physicochemical properties for priority chemicals and bioconcentration data are also reported. The information provided in this report establishes a good data base, to assist the Ontario Ministry of the En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 72 publications
1
31
0
1
Order By: Relevance
“…new. Various authors have demonstrated the existence of mathematical relationships between the buffer-membrane and buffer-octanol partition coefficients in a very quantitative way.23.24 Gabas et al 23 were able to show that for molecules having a molar volume of <300 cm3/mol, as is the case here (Table III), the correlation between the two coefficients was regular and increasing. It seems essential to add that simply considering the partition coefficient POlw does not make it possible to determine the interactions and localization of the drug within a membrane-like organization.…”
Section: Resultsmentioning
confidence: 55%
“…new. Various authors have demonstrated the existence of mathematical relationships between the buffer-membrane and buffer-octanol partition coefficients in a very quantitative way.23.24 Gabas et al 23 were able to show that for molecules having a molar volume of <300 cm3/mol, as is the case here (Table III), the correlation between the two coefficients was regular and increasing. It seems essential to add that simply considering the partition coefficient POlw does not make it possible to determine the interactions and localization of the drug within a membrane-like organization.…”
Section: Resultsmentioning
confidence: 55%
“…Integrating gives /f =fJDJ{Dw + Dm)]{l -exp[-(Dw + Dm)t/VFZF}} (5) The concentration in the fish is then CF or ZF/F at any time. This uptake equation is commonly expressed in rate constant form as (39): (6) It can be shown that k\ is Dw/ VFZW, k2 is Dw/VfZf, and km is Dm/VFZp (18).…”
Section: Resultsmentioning
confidence: 99%
“…The model is a non‐steady‐state mass balance model for hydrophobic organic chemicals based on a Lake Ontario food chain. The food chain bioaccumulation model was proposed and enhanced by Gobas as well as Arnot and Gobas (2004) , . The models assumption is that the change in concentration of a chemical in an organism with time is a result of the rate of uptake and loss of the chemical.…”
Section: Abatement Technologiesmentioning
confidence: 99%